Comparative Study of the Implementation of Mathematical Literacy in the Merdeka Curriculum at the Junior High School Level - Sapitri, Lenny; Sukirman, Dadang (Lembaran Ilmu Kependidikan, 2023)
The low mathematical literacy of Indonesian students has prompted curriculum changes aimed at improving this ability. Judging from the implementation of the curriculum in Indonesia, there are differences in the implementation of the curriculum in public and private schools. This difference is because the education unit has an implementation strategy. This study aims to determine the differences in the implementation of mathematical literacy in the Merdeka curriculum which is focused on the junior high school level. The method used in this study is a comparative method with a qualitative approach. Data in this study were collected through questionnaires and interviews. The data analysis technique used is interactive analysis consisting of data collection, data reduction, data presentation, conclusion drawing, and verification stages. The results obtained in this study were that there were differences in the implementation of the Merdeka curriculum's mathematical literacy at the junior high school level. The difference lies in the frequency with which teachers attend training and assistance in planning, implementing and evaluating learning, as well as the variety of methods, media and learning tools used. The results obtained in this study can provide an overview regarding the planning, implementation, and assessment carried out to improve mathematical literacy.